2012
DOI: 10.1163/156855511x606128
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photopolymerization of 2,2-Di((Acryloyloxy)Methyl)Butyl Bis(2-(Acryloyloxy)Ethyl)Carbamate

Abstract: A low-viscosity monomer, 2,2-di((acryloyloxy)methyl)butyl bis(2-(acryloyloxy)ethyl)carbamate (DBAC), was synthesized using a non-isocyanate route. The photopolymerization kinetics were monitored by realtime infrared spectroscopy (RT-IR). The results indicated that the rate of polymerization and the final conversion of DBAC were high and influenced by light intensity, photoinitiator type and concentration. Dynamic mechanical analysis (DMA) results indicated that the glass transition temperature and molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In these TMPCs, the TMPC having non-modified hydroxyl groups (TMPC2) or the TMPC in which its hydroxyl group is modified with phenoxycarbonyl groups (TMPC3) have been already reported. 15,17,[40][41][42][43][44] However, these two TMPCs are synthesized from TMP using dimethyl carbonates, lipases with a catalyst or using phenyl chloroformates, which are different from our approach using less toxic and easily-handled DPC. Interestingly, other structured TMPC (TMPC1) which is less soluble in EtOAc was isolated in relatively good yields.…”
Section: Reaction Of Tmp With Dpcmentioning
confidence: 92%
See 1 more Smart Citation
“…In these TMPCs, the TMPC having non-modified hydroxyl groups (TMPC2) or the TMPC in which its hydroxyl group is modified with phenoxycarbonyl groups (TMPC3) have been already reported. 15,17,[40][41][42][43][44] However, these two TMPCs are synthesized from TMP using dimethyl carbonates, lipases with a catalyst or using phenyl chloroformates, which are different from our approach using less toxic and easily-handled DPC. Interestingly, other structured TMPC (TMPC1) which is less soluble in EtOAc was isolated in relatively good yields.…”
Section: Reaction Of Tmp With Dpcmentioning
confidence: 92%
“…Generally, TMP is used as a cross-linker or a core of star-shaped, hyperbranched or networked polymers. 30,39,40 It is also reported that 6-CCs are synthesized from TMP using phosgene derivatives and are polymerized to form hyperbranched polycarbonates. 41 However, it is rarely reported that PHUs are synthesized from TMP-based cyclic carbonates except for a few cases.…”
Section: Introductionmentioning
confidence: 99%
“…Other uses include manufacturing solder mask, stereolithography, and microelectronic photoresists. In addition, quick-setting adhesives, coatings, sealants, and the production of composite materials are just some of the many applications of photopolymerization [ 1 , 2 , 3 ]. So many applications result from the high speed of curing by UV radiation and the high efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%